2009
DOI: 10.1089/jpm.2008.0196
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Physician Orders for Life-Sustaining Treatment (POLST) Paradigm Program in the Hospice Setting

Abstract: Background: The Physician Orders for Life-Sustaining Treatment (POLST) Paradigm Program was designed to ensure the full range of patient treatment preferences are honored throughout the health care system. Data are lacking about the use of POLST in the hospice setting. Objective: To assess use of the POLST by hospice programs, attitudes of hospice personnel toward POLST, the effect of POLST on the use of life-sustaining treatments, and the types of treatments options selected by hospice patients. Design: A tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
98
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(105 citation statements)
references
References 16 publications
0
98
2
1
Order By: Relevance
“…As others have reported, 4 the amounts of treatment decedents received varied significantly depending on the orders indicated in the Treatment Options section (Section B) of the POLST form. In our study, however, patients with orders for Additional Limited Intervention and Aggressive Treatment were somewhat more likely to receive treatment, even though in our study we did not track chemotherapy, radiation treatments, or invasive diagnostic tests as life-sustaining treatments as was done in the previous study.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…As others have reported, 4 the amounts of treatment decedents received varied significantly depending on the orders indicated in the Treatment Options section (Section B) of the POLST form. In our study, however, patients with orders for Additional Limited Intervention and Aggressive Treatment were somewhat more likely to receive treatment, even though in our study we did not track chemotherapy, radiation treatments, or invasive diagnostic tests as life-sustaining treatments as was done in the previous study.…”
Section: Discussionmentioning
confidence: 89%
“…3 A study of hospice patients found a high rate of consistency between treatments provided and POLST orders. 4 A recent retrospective study 5 compared the use of POLST with the standard approach of writing medical orders for 1711 long-term care residents in three states. Looking only at POLST use in these nursing homes, this study determined that residents with POLST forms had significantly more medical orders regarding life-sustaining treatment than residents without POLST forms.…”
mentioning
confidence: 99%
“…8 POLST offers advantages over traditional code status orders by permitting documentation of a wide range of treatment preferences including resuscitation, medical interventions such as hospitalization, antibiotics, and artificial nutrition. [9][10][11][12][13] It is recommended that the POLST be generated before hospital discharge for eligible patients 14 to help ensure that patients have orders available during transport and upon arrival at the facility or home. When patients lack decisional capacity and there are no orders available reflecting prior treatment decisions, the default is to provide all available medical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…37 Tracking this innovation as a natural experiment, investigators have found evidence that POLST is effective to facilitate care consistent with preferences for older patients in nursing homes, PACE, and hospice. [38][39][40] Can Interventions Improve the Quality of Decision Making?…”
Section: -31mentioning
confidence: 99%